2008
DOI: 10.1017/s0016756808004585
|View full text |Cite
|
Sign up to set email alerts
|

Onset of the Ordovician cephalopod radiation – evidence from the Rochdale Formation (middle Early Ordovician, Stairsian) in eastern New York

Abstract: The Rochdale Formation of eastern New York (= Fort Ann and lower Bascom formations, designations abandoned) is now recognized to record the earliest stages of the Great Ordovician Radiation of cephalopods. The earliest Bassleroceratidae, Tarphyceratidae and endoceridans on the east Laurentian shallow carbonate platform occur in the upper, thrombolite-bearing member of the Rochdale. This fauna demonstrates that the earliest radiation of Ordovician nautiloids took place in the late Tremadocian and is best record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…Tarphycerids (Early Ordovician-late Silurian) with tightly coiled conchs are the oldest cephalopods with a supposedly nektonic mode of life resembling extant Nautilus (Kröger 2005, Kröger & Landing 2008. The time of hatching can be determined in fossil nautiloids by applying an actualistic approach using information from the early embryonic development of extant Nautilus (Stenzel 1964, Mutvei et al 1993, Mutvei & Doguzhaeva 1997).…”
Section: Hatching Indication In Tarphyceridsmentioning
confidence: 99%
“…Tarphycerids (Early Ordovician-late Silurian) with tightly coiled conchs are the oldest cephalopods with a supposedly nektonic mode of life resembling extant Nautilus (Kröger 2005, Kröger & Landing 2008. The time of hatching can be determined in fossil nautiloids by applying an actualistic approach using information from the early embryonic development of extant Nautilus (Stenzel 1964, Mutvei et al 1993, Mutvei & Doguzhaeva 1997).…”
Section: Hatching Indication In Tarphyceridsmentioning
confidence: 99%
“…The Emanuel Limestone also contains taxa that suggest links with higher latitude cephalopod assemblages. Whilst Eothinoceras Ulrich et al, 1944 may be widely distributed across low latitude carbonate platforms during the late Tremadoc and early Floian; the genus having first been described from the Rochdale Limestone of New York (Ulrich et al 1944;Kraeger & Landing 2008), then from the Canning Basin (Teichert & Glenister 1954), North China (Chen & Teichert 1987) and Bolivia (Cecioni & Flower 1985;Evans 2007). Evans (2005,2007) suggested that Protocycloceras contrarium Teichert & Glenister from the Emanuel Limestone might in fact be a Saloceras given the well-developed ventral saddle and remarkably thick connecting rings.…”
Section: Paleogeographic Relationshipsmentioning
confidence: 99%
“…Landing, 2007;Kröger & Landing, 2008;Landing et al 2010) (Fig. Landing, 2007;Kröger & Landing, 2008;Landing et al 2010) (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…1). Kröger & Landing (2008) recognized two informal divisions of the Rochdale, a 'lower member' and an upper 'thrombolitic member'. Kröger & Landing (2008) recognized two informal divisions of the Rochdale, a 'lower member' and an upper 'thrombolitic member'.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation